The effect of AqueousExtractofElaeagnusangustifolia on Diabetic Neuropathic Pain in Streptozotocin-induced Diabetic Rats - Omid Reza Tamtaji; SayedAlireza Talaei; Mohsen Taghizadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2015)
Background and Objectives:One of the common complications of diabetes is nervous system disorder and diabetic neuropathy. In various studies, it has been reported that flavonoid and polyphenolic compounds of plants improve diabetic neuropathy. Due to the presence of large amounts of these compounds in Elaeagnusangustifolia fruit, thisstudywas performedwith the aim of investigating the effect of aqueous extract of Elaeagnusangustifolia on diabetic neuropathic pain in streptozotocin-induced diabetic rats.